IMPACT OF CYBER LAWS ON FREEDOM OF EXPRESSION (Contemporary Journal of Social Science Review, 2025)
The rapid expansion of digital technologies has transformed communication and public participation, making cyberspace a vital arena for democratic expression. However, the increasing adoption of cyber laws has raised concerns regarding their impact on freedom of expression. This study investigates how cyber laws influence individuals’ online behaviors and perceptions. Using a mixed‑methods design, the study surveyed 250 respondents and conducted semi‑structured interviews with 10 participants. Results reveal moderate awareness of cyber laws but significant fear of surveillance, legal repercussions, and ambiguity in digital regulations. Self‑censorship was found to be prevalent, especially in political and institutional contexts. The discussion draws from global literature to contextualize the findings, emphasizing the need for rights‑based, transparent, and proportionate cyber governance. Recommendations include improving public awareness, refining legal language, and ensuring judicial oversight. The study concludes that while cyber laws are essential for safety, they must not undermine democratic freedoms.